Ação do óleo essencial de pimenta-rosa ("Schinus terebinthifolius") no desenvolvimento in vitro de "Colletotrichum truncatum", agente causal da antracnose da soja ("Glycine max") - Araujo, Ana Carolina (Universidade Federal de São Carlos, 2021)
the soybean is one of the most economically important crops in the world and has been cultivated by thousands of family farmers, especially in the southern region of the country. Crop productivity can be threatened by various types of pathogens that cause various diseases, including anthracnose, caused by the fungus Colletotrichum truncatum. One of its main control methods has been the application of fungicides in crops, which contributes to increasing environmental insecurity and concern for the health of the population. In this sense, the use of vegetable oils in phytopathogenic control can be an interesting alternative to replace such chemicals. The present study aimed to evaluate the effect of the essential oil of pink pepper (Schinus terebinthifolius) on the in vitro growth of colonies of the fungus Colletotrichum truncatum, the causal agent of anthracnose in soybean. The essential oil was applied in different ways to the Potato-Dextrose-Agar (BDA) culture medium in separate Petri dishes. Then, mycelial disks of the fungus were plated and their growth evaluated at 3, 5, 7 and 9 days. The results show that the greatest control of the growth of the pathogen occurs in T3 (essential oil on the surface), usually followed by T4 (filter paper). In addition, from 500 μl to 800 μl, approximately 1 centimeter of growth was suppressed on the 9th day.
Action of the essential oil of pink pepper (Schinus terebinthifolius) in development of Colletotrichum truncatum, causal agent of soybean anthracnosis (Glycine max)
Keywords: Manejo ecológico; Controle alternativo; Pimenta-rosa; Fungo fitopatogênico; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE